2016
DOI: 10.1111/1365-2664.12814
|View full text |Cite
|
Sign up to set email alerts
|

Local tropical forest restoration strategies affect tree recruitment more strongly than does landscape forest cover

Abstract: Summary1. Developing restoration strategies that accelerate natural successional processes and are resource-efficient is critical to facilitating tropical forest recovery across millions of hectares of deforested lands in the tropics. 2. We compared tree recruitment after a decade in three restoration treatments (natural regeneration, applied nucleation/island tree planting and plantation) and nearby reference forest in the premontane rain forest zone in southern Costa Rica. The study was replicated at 13 site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 67 publications
7
107
1
13
Order By: Relevance
“…found differences in species composition between tree plantations and secondary forest at 10 and 15 years old (Butler et al, 2008;Holl et al, 2017), although a study of 5-year-old sites did not (Gilman et al, 2016). Although regeneration in tree plantations is often dominated by early successional species (Cusack & Montagnini, 2004;Zahawi et al, 2013), it has been shown to resemble the composition of mature forest more than secondary forest does .…”
Section: Effects Of Forest Type On Species Compositionmentioning
confidence: 94%
“…found differences in species composition between tree plantations and secondary forest at 10 and 15 years old (Butler et al, 2008;Holl et al, 2017), although a study of 5-year-old sites did not (Gilman et al, 2016). Although regeneration in tree plantations is often dominated by early successional species (Cusack & Montagnini, 2004;Zahawi et al, 2013), it has been shown to resemble the composition of mature forest more than secondary forest does .…”
Section: Effects Of Forest Type On Species Compositionmentioning
confidence: 94%
“…One combined approach is applied nucleation , which involves planting small patches of vegetation (often trees) that attract dispersers and facilitate establishment of new recruits, expanding the forested area over time. Applied nucleation has shown promise in restoring landfills (Corbin et al ), Mediterranean woodlands (Rey Benayas et al ), tropical forests (Corbin & Holl ; Holl et al ), and other ecosystems. Deciding on an appropriate approach or combination may not be self‐evident.…”
Section: Section 4—leading Practicesmentioning
confidence: 99%
“…This result is consistent with the limited woody recruitment and aboveground biomass quantified in these plots, which is most likely due to competition with pasture grasses (Holl & Zahawi , Holl et al . ); a possible alternative is slower growth rates at our premontane wet forest sites. Brown and Lugo () conclude that litterfall is highest at an intermediate ratio of temperature to precipitation; however, our sites have comparatively lower temperature to lowland sites where most tropical secondary forest litterfall studies have been conducted ( e.g ., Ewel , Ostertag et al .…”
Section: Discussionmentioning
confidence: 88%
“…, Holl et al . ), but at least in the short‐term results in less aboveground biomass (Holl & Zahawi ).…”
mentioning
confidence: 99%
See 1 more Smart Citation